ANALISIS PENENTUAN HARGA JUAL AIR MINERAL MASKUA DI KOTA SINGKAWANG - Suandari, Yulita; Afif, Ali; Jaurino, Jaurino; Carolin, Angelina (Program Studi Akuntansi Universitas Panca Bhakti, 2024)
In this study, researchers conducted research on planning and controlling production costs by calculating the selling price of Maskua mineral water at PT. Pakunam Tirtajaya Perkasa Singkawang City precisely and accurately while maintaining the quality of the goods or products produced. Method full costing is a method of determining the cost of production that takes into account all elements of production costs into the cost of production, which consists of raw material costs, direct labor costs and factory overhead costs, both variable and fixed. In determining the calculation of the cost of production for the Maskua mineral water company, it has not calculated production costs in accordance with accounting principles which consist of raw material costs, labor costs, and fixed and variable factory overhead costs. The cost of production according to the company shows different results because the company charges raw materials as the basis for determine the cost of production per type of product. Whereas Calculations for determining the cost of production based on the full costing method obtain a higher value, because full costing calculates all cost elements, both fixed costs and variable costs, which are included in the product produced. Thus, it can be concluded from the explanation above that the profit obtained by the company is higher when compared to the profit obtained using metode cost plus pricing.